1991
DOI: 10.1002/casp.2450010305
|View full text |Cite
|
Sign up to set email alerts
|

Police officers' definitions of rape: A prototype study

Abstract: The study investigates police officers' definitions of different rape situations. On the basis of the concept of ‘cognitive prototypes’ a methodology is developed which elicits consensual feature lists describing six rape situations: the typical, i.e. most common rape, the credible, dubious, and false rape complaints as well as the rape experiences that are particularly hard vs. relatively easy for the victim to cope with. Qualitative analysis of the data allows the identification of the characteristic feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 41 publications
3
35
0
Order By: Relevance
“…The perpetrator is described as using physical aggression, is mentally or socially unfit, and is totally responsible for the incident. This finding was replicated by Krahé (1991), who found that police officers also described a typical rape as involving a stranger who attacks outdoors with a moderate degree of physical force.…”
supporting
confidence: 58%
“…The perpetrator is described as using physical aggression, is mentally or socially unfit, and is totally responsible for the incident. This finding was replicated by Krahé (1991), who found that police officers also described a typical rape as involving a stranger who attacks outdoors with a moderate degree of physical force.…”
supporting
confidence: 58%
“…Laypersons and prosecutors might be more likely to envision severe sex offender stereotypes. In fact, research suggests that people often have a violent prototype of sex offenders (Finkel & Groscup, 1997;Krahé, 1991), envisioning an offender who forces unwilling individuals to engage in sexual acts (Quinn, Forsyth, & Mullen-Quinn, 2004). Prototypes and stereotypes have been shown to influence legal decision-making in other types of case involving juvenile offenders.…”
Section: Understanding the Effect Of Offender Age On Family Law Attormentioning
confidence: 98%
“…Finally, the high degree of mismatch between individuals' rape scripts and most marital rapes helps explain why individuals may believe that husbands cannot rape their wives. Supporting the role of rape scripts in understanding these rape myths, Krahé (1991) evaluated German police officers' scripts for different types of rape and found that officers described the typical rape as a moderately violent stranger assault. In contrast, rapes that deviated from this script, such as those that occurred in the context of consensual activity, involved an assailant or victim who were acquainted, or that involved heavy alcohol use, were regarded as dubious or false.…”
Section: Rape Scriptsmentioning
confidence: 99%